2018
DOI: 10.18203/2349-3291.ijcp20183518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of children presenting with poisoning or intoxication: a hospital-based study

Abstract: Background: Poisoning is a common preventable cause of morbidity and mortality in children. Most of the poisoning in children less than 5 years of age is accidental. Not much of Indian data is available particularly from this part of the country. So, authors conducted a retrospective hospital record-based study to know clinical profile and outcome of children presenting with poisoning in our set up. The objective was to study clinical profile, outcome of childhood poisoning and intoxication in Jammu District (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In the present study, males outnumbered females. Male dominance could be due to more aggressive and exploratory nature and their greater degree of activity (Qazi and Saqib, 2018). Other studies showed similar age and gender predominance were reported by Al-Naddawi et al, (2009) in Iraq, Anwar et al, (2014) in Bangladesh, Kumaravel and Rameshbabu (2016) in India, and by Singh and Gurung, (2018) in Pakistan.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the present study, males outnumbered females. Male dominance could be due to more aggressive and exploratory nature and their greater degree of activity (Qazi and Saqib, 2018). Other studies showed similar age and gender predominance were reported by Al-Naddawi et al, (2009) in Iraq, Anwar et al, (2014) in Bangladesh, Kumaravel and Rameshbabu (2016) in India, and by Singh and Gurung, (2018) in Pakistan.…”
Section: Discussionsupporting
confidence: 63%
“…The present work highlighted that 22.1% were discharged against medical advice (DAMA) after taking the consent of their legal guardian. Qazi and Saqib, (2018) demonstrated that some of kerosene poisoning cases left the hospital against medical advice as they consumed small quantities and were admitted for observation.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,15 Quazi et al reported that 13 to 18 years was commoner age for poisoning and mostly intentional. 16 It is already reported in literatures that below 5 year of age children are prone to accidental poisoning due to their curious nature, habit of mouthing and innocence. In all studies, below 5 years of age accidental poisoning was most common presentation as reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates that kerosene is the most frequent domestic fuel used by lower middle-class households, and that because it is kept in bottles on the kitchen floor, children readily drink the bottles as water or play with them out of curiosity. Other research from Moradabad performed by Ravi Gangal et al 19 and Mahvish Qazi et al 20 , revealed insecticides and pesticides to be the most often ingested material, while another study conducted in Pakistan 21 found pharmaceuticals to be the most prevalent poisoning agent. Mineral spirit or paint thinner, which is commonly used with paints for painting homes, is the second most common agent involved.…”
Section: Discussionmentioning
confidence: 93%